Guarantee of Legal Protection for Conventional and Electronic Land Rights Certificates Holders within The Land Registration Legal System in Indonesia - Lily Andayani; Arif Firmansyah (Jurnal Daulat Hukum, 2026)
Land rights certificates constitute strong and highly significant evidence of land ownership. This study aims to examine legal certainty and legal protection for holders of land rights certificates in both conventional and electronic forms. The transition from a conventional system to a digital one gives rise to significant legal consequences for land rights holders. Legal protection is intended to safeguard land rights that may be harmed by other individuals or parties. This research employs a normative juridical approach, conducted through the examination and analysis of legal provisions, legal principles, and statutory regulations relevant to the subject of the study. With the enactment of Government Regulation Number 18 of 2021, a new form of land rights certificate has been introduced, namely the electronic certificate. However, this regulation does not revoke Government Regulation Number 24 of 1997. Consequently, conventional land certificates remain valid as long as no application for a change in certificate form is submitted or no transfer of land rights occurs. The simultaneous application of these two Government Regulations has the potential to create regulatory overlap, which may undermine legal certainty and legal protection for holders of land rights certificates. Therefore, the establishment of regulations of equal or higher hierarchical status is necessary to strengthen legal certainty and legal protection.